Biología y recursos alimenticios usados por el género de abejas Cephalotrigona Schwarz 1994 - García Sánchez, Daniel Josué (2023)
SUMMARY The genus Cephalotrigona includes robust bees of relatively large size (6 to 10 mm) characterized by strong and large stippling on the clipeus, supraclipeal region, paraocular region and lower part of the genas that contrasts with a matte and reticulated integument of the rest of the head and mesoscutum; the workers have mandibles with a single well developed tooth on the inner third of the apical edge. The information that was developed was through the meticulous sketch of technical information, based on the analysis, synthesis and summary, with the purpose of generating reliable ideas in accordance with this study, whose theme is "Biology and food resources used by the genus of bees Cephalotrigona spp. It was determined through the compilation of information in 48 sources of which 35 were scientific articles and 13 degree theses, it was evidenced that several species of the genus Cephalotrigona have a diverse food resource in plant species of different families such as: Actinidaceae, Arecaceae, Asteraceae, Clusiaceae, Euphorbiaceae, Fabaceae, Hypericaceae, Juglandaceae, Loranthaceae, Lythraceae, Melastomataceae, Muntigiaceae, Myrtaceae, Oleaceae, Primulaceae, Rutaceae, Sapindaceae, Solanaceae, Tiliaceae, Urticaceae, Verbenaceae,p Viscaceae, Vitaceae, Apocynaceae, Malvaceae, Cactaceae, Boraginaceae, Bixaceae, Lamiaceae, Convolvulaceaee, Mimosaceae, Nyctaginaceae, Moraceae, Moringaceae, Anacardiaceae, Lauraceae, Anacardiaceae, Rubiaceae, Burseraceae, Annonaceae. The studied species C. capitata (Smith, 1854), C. eburneiventer (Schwarz, 1948) and C. zexmeniae (Cockerell, 1912) obtain their food resources (nectar and pollen) from a diversity of plant species. Bees of the genus Cephalotrigona belong to a group of social insects inhabiting tropical and subtropical regions, especially forest areas. Stingless bees of the genus Cephalotrigona are a diverse group with great cultural value, economic potential and ecological importance; besides being a source of useful products for humans, they are important pollinators of natural and agricultural systems.